Factors affecting survival and cause-specific mortality of saiga calves in Mongolia - Buuveibaatar, Bayarbaatar; Young, Julie K.; Berger, Joel; Fine, Amanda E.; Lkhagvasuren, Badamjav; Zahler, Peter; Fuller, Todd K. (DigitalCommons@University of Nebraska - Lincoln, 2013)
Factors affecting juvenile survival are poorly known in the world’s most northern antelope, the endangered saiga (Saiga tatarica), yet these factors are fundamental for understanding what drives population change. We monitored Mongolia saiga (S. tatarica mongolica) calves in Sharga Nature Reserve, western Mongolia, during 2008–2010. Our results showed that male and single calves were heavier than females and twins, respectively. However, we identified no significant differences in seasonal or annual survival rates between sexes or between singletons and twins. Litter size and birth mass varied among years, and there was a negative relationship between these variables. Survival of calves during the 1st year was best explained by the covariates of year and litter size (confounded with body mass), suggesting that interannual variation in environmental conditions influenced twinning rates and body mass, and might play a key role in 1st-year survival. We identified 3 sources of mortality—predation by raptors, foxes (red fox [Vulpes vulpes] and corsac fox [V. corsac]), and lynx (Lynx lynx). Most predation was attributed to raptors, such as golden eagles (Aquila chrysaetos) and cinereous vultures (Aegypius monachus). Our results point to both environmental and biotic factors affecting survival of juvenile saiga.